The Influence of the Project Based Learning (PjBL) Learning Model in Civics Subjects on the Development of Students' Civic Skills at SMP Muhammadiyah 19 Pematangsiantar TP. 2022/2023 - Nisa, Khairun; Amin, Zulkifli (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2023)
This research aims to find out the influence of the Project Based Learning (PjBL) learning model in Civics subjects on the development of student’s civic skills. This research uses quantitative research. The objects of this research were class VIII students of SMP Muhammadiyah 19 Pematangsiantar and data collection techniques used questionnaires, observation and documentation. The data analysis techniques used are validity tests, reliability tests, normality tests, and using the